Bridging the divide: the role of HBCU law schools in addressing the equitable development goals of US metropolitan areas - Akintobi, Adeshola; O’Hara, Sabine; Harrison, Elgloria; Brittain, John (Frontiers in Sustainable Cities, 2025)
IntroductionThis article explores clinical law programs of Historically Black Colleges and Universities (HBCU) and their role in advancing equitable development in urban communities which have been impacted by disinvestment, redlining, and gentrification. Building on the legacy of the Great Migration and subsequent urban decline, the communities where the six HBCU law schools, accredited by the American Bar Association (ABA), are located have experienced a range of development challenges. They are Orlando, Florida, Durham, North Carolina, Washington, D. C., Houston, Texas, and Baton Rouge, Louisiana. The study examines whether these law schools deliver what their stated priorities promise, namely, to meaningfully contribute to the equitable development goals of the communities where they are located.MethodsUsing a systematic review of publicly available documents as well as case study materials from the five metro areas, the study reveals a strong alignment between the clinical work offered by the law schools in our sample and the development needs of the metropolitan areas where they are located.ResultsThese alignments are particularly evident in the areas of affordable housing, youth advocacy, immigration, and economic justice.DiscussionWhile the study is limited by its reliance on publicly available data, the findings suggest that HBCU law schools and their clinical programs provide critical contributions to the civic infrastructure of US metropolitan areas seeking to achieve equitable urban revitalization. The findings also identify opportunities for further research, to investigate the dynamics between law school clinical programs and equitable community development in more depth.